Visual Communication in Environmental Education: A Semiotic Analysis of Instagram Content from @walhisulteng and @dlh.sultengprov - Gavil, Muhamad; Zainuddin, Sumarni; Herawati N, Andi Febri (Global Writing Academica Researching & Publishing, 2026)
This study aims to analyze visual signs (icons, indices, and symbols) in the Instagram content of @walhisulteng in shaping environmental education related to issues of environmental degradation in Central Sulawesi Province; to analyze visual signs (icons, indices, and symbols) in the Instagram content of @dlh.sultengprov in shaping environmental education related to waste management issues in Central Sulawesi Province; and to examine the semiotic differences between the content of @walhisulteng and @dlh.sultengprov in conveying environmental messages on Instagram. This research employs a descriptive qualitative approach within an interpretive paradigm and applies Charles Sanders Peirce’s semiotic analysis as the primary analytical framework. The research data were obtained through documentation of visual Instagram content, including image posts and infographics addressing environmental issues. The analysis was conducted by identifying visual representamen, classifying signs into icons, indices, and symbols, and interpreting the objects and interpretants produced. The findings indicate that visual signs in the form of icons, indices, and symbols in the Instagram content of @walhisulteng and @dlh.sultengprov construct meanings of environmental education related to issues of environmental degradation and waste management in Central Sulawesi Province. Icons function as representations of environmental objects, indices indicate cause-and-effect relationships related to environmental conditions, and symbols reinforce messages through the use of established visual conventions. The relationships among these visual signs contribute to building audience understanding of environmental education messages conveyed through graphic design on Instagram as a social media platform.